A Critical Discourse Analysis of the Iraqi October Revolution in BBC News Channel - Al-Azzawi, Qasim Obayes; Rahi, Hawraa Jabbar (International Journal of Psychosocial Rehabilitation, 2020)
Power and ideology attract the attention of most, if not all, discourse analysts for their importance in squeezing the idea behind using certain linguistic constructions rather than others. The present study is an endeavour to plant a critical seed in the land of BBC news reports to examine their language, mainly in terms of the Iraqi October revolution 2019-2020. It, therefore, basically aims at identifying the structure of the analytical framework of BBC news discourse as far as Iraqi October Revolution is concerned. In accordance with its aims, this study hypothesises that the structure of the analytical framework of BBC news discourse is mapped in terms of three dimensions: the successive structure of the news reports, the discourse strategies, and the social practice from a critical discourse perspective. For the sake of achieving its aims and testing the validity of its hypotheses, the present study follows certain steps. It mainly reviews the pertinent literature about CDA in relation to Iraqi October revolution. Moreover, it analyses three news reports as representative examples via a model developed in this study for this purpose. The study at hand has winded up at some conclusions, the most essential of which is that the structure of the analytical framework of BBC news reports are structured in terms of micro-analysis and macro-analysis to provide the discourse strategies and the effects of power and ideology from the angle of CDA.